Norm inequalities in multidimensional Lorentz spaces - Simonov, Boris; Tikhonov, Sergey (MATHEMATICA SCANDINAVICA, 2008)
In this paper we obtain necessary and sufficient conditions for double trigonometric series to belong to generalized Lorentz spaces, not symmetric in general. Estimates for the norms are given in terms of coefficients.